2017
DOI: 10.1021/acs.langmuir.6b04435
|View full text |Cite
|
Sign up to set email alerts
|

Robust Alginate-Catechol@Polydopamine Free-Standing Membranes Obtained from the Water/Air Interface

Abstract: The formation of polydopamine composite membranes at the water/air interface using different chemical strategies is reported. The use of either small molecules (urea, pyrocatechol) or polymers paves the way to understand which kind of compounds can be used for the formation of PDA-composite free-standing membranes produced at the water/air interface. On the basis of these screening results, we have found that alginate grafted with catechol groups allows the formation of robust free-standing films with asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Such films are nevertheless extremely brittle. They can be consolidated from a mechanical point of view using poly(ethylene imine) (Hong et al, 2014 ; Yang et al, 2014 ) or alginate modified with catechol groups (Ponzio et al, 2017 ) to yield extremely thick (hundreds of nanometers), flexible, anisotropic, and humidity-responsive membranes.…”
Section: Oxidation Of Catecholamines and Its Consequences On Surfacesmentioning
confidence: 99%
“…Such films are nevertheless extremely brittle. They can be consolidated from a mechanical point of view using poly(ethylene imine) (Hong et al, 2014 ; Yang et al, 2014 ) or alginate modified with catechol groups (Ponzio et al, 2017 ) to yield extremely thick (hundreds of nanometers), flexible, anisotropic, and humidity-responsive membranes.…”
Section: Oxidation Of Catecholamines and Its Consequences On Surfacesmentioning
confidence: 99%
“…In the case of alginate derivatives, previous reports obtained catechol contents ranging from 5% to 15% using a feed ratio of carboxylate to catechol of 1:1 [ 32 , 35 , 38 ]. Because this study used a 3:1 ratio, a higher content of catechol in the alginate was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Various concentrations of AC and GC were dissolved in 10 mM Tris-HCl buffer (pH = 8.5); gel formation was observed at concentrations over 20 mg/mL after 16 h for both AC and GC. In a previous report, above an AC concentration of 30 mg/mL, a hydrogel formed in the presence of dopamine [ 32 ]. Additionally, it has also been reported that cross-linking of AC was accelerated to form a hydrogel under basic conditions in the presence of the chemical oxidizing agent sodium periodate (NaIO 4 ); equimolar amounts of NaIO 4 and catechol in AC resulted in the formation of a hydrogel within 3–4 min after induction of gelation [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freestanding PDA films with a thickness of several hundreds of nanometers or even micrometers have been synthesized before. [ 20–27 ] Ultrathin and homogeneous PDA films attached to gold surfaces with thicknesses of 5–20 nm have been prepared by electropolymerization. [ 28 ] Electropolymerization is considerably faster than the often applied dip coating procedure, allowing precise control of the film thickness and homogeneity.…”
Section: Introductionmentioning
confidence: 99%